Plasmodium cellular effector mechanisms and the hepatic microenvironment - Frevert, Ute; Krzych, Urszula (Frontiers in Microbiology, 2015)
Plasmodium falciparum malaria remains one of the most serious health problems globally. Immunization with attenuated parasites elicits multiple cellular effector mechanisms capable of eliminating Plasmodium liver stages. However, malaria liver stage immunity is complex and the mechanisms effector T cells use to locate the few infected hepatocytes in the large liver in order to kill the intracellular liver stage parasites remain a mystery to date. Here, we review our current knowledge on the behavior of CD8+ effector T cells in the hepatic microvasculature, in malaria and other hepatic infections. Taking into account the unique immunological and lymphogenic properties of the liver, we discuss whether classical granule-mediated cytotoxicity might eliminate infected hepatocytes via direct cell contact or whether cytokines might operate without cell-cell contact and kill Plasmodium liver stages at a distance. A thorough understanding of the cellular effector mechanisms that lead to parasite death hence sterile protection is a prerequisite for the development of a successful malaria vaccine to protect the 40% of the world’s population currently at risk of Plasmodium infection.